Evolutionary diversification of the canonical Wnt signaling effector TCF/LEF in chordates. (3rd February 2022) - Torres‐Aguila, Nuria P.; Salonna, Marika; Hoppler, Stefan; Ferrier, David E. K.
Abstract: Wnt signaling is essential during animal development and regeneration, but also plays an important role in diseases such as cancer and diabetes. The canonical Wnt signaling pathway is one of the most conserved signaling cascades in the animal kingdom, with the T‐cell factor/lymphoid enhancer factor (TCF/LEF) proteins being the major mediators of Wnt/β‐catenin‐regulated gene expression. In comparison with invertebrates, vertebrates possess a high diversity of TCF/LEF family genes, implicating this as a possible key change to Wnt signaling at the evolutionary origin of vertebrates. However, the precise nature of this diversification is only poorly understood. The aim of this study is to clarify orthology, paralogy, and isoform relationships within the TCF/LEF gene family within chordates via in silico comparative study of TCF/LEF gene structure, molecular phylogeny, and gene synteny. Our results support the notion that the four TCF/LEF paralog subfamilies in jawed vertebrates (gnathostomes) evolved via the two rounds of whole‐genome duplications that occurred during early vertebrate evolution. Importantly, gene structure comparisons and synteny analysis of jawless vertebrate (cyclostome) TCF s suggest that a TCF7L2‐ like form of gene structure is a close proxy for the ancestral vertebrate structure. In conclusion, we propose a detailed evolutionary path based on a new pre‐whole‐genome duplication vertebrate TCF gene model. This ancestor gene model highlights the chordate and vertebrate innovations of TCF/LEF gene structure, providing the foundation for understanding the role of Wnt/β‐catenin signaling in vertebrate evolution. Abstract : The canonical Wnt/β‐catenin signaling pathway acts through the TCF/LEF family of transcription factors. The step change in diversity of the genes in this family across the invertebrate–vertebrate transition is described here, via a new evolutionary model that includes the inferred intermediate genes in this transition. This provides a foundation for future work on the functional diversity of these genes in development and disease.